Microwave absorption properties of reduced graphene oxide strontium hexaferrite/poly(methyl methacrylate) composites. (6th February 2018) - Acharya, Sanghamitra; Ray, J; Patro, T U; Alegaonkar, Prashant; Datar, Suwarna
Abstract: The key factors to consider when designing microwave absorber materials for eradication of electromagnetic (EM) pollution are absorption of incident EM waves and good impedance matching. By keeping these things in mind, flexible microwave absorber composite films can be fabricated by simple gel casting techniques using reduced graphene oxide (RGO) and strontium ferrite (SF) in a poly(methyl methacrylate) (PMMA) matrix. SF nanoparticles are synthesized by the well known sol–gel method. Subsequently, reduced graphene oxide (RGO) and SF nanocomposite (RGOSF) are prepared through a chemical reduction method using hydrazine. The structure, morphology, chemical composition, thermal stability and magnetic properties of the nanocomposite are characterized in detail by various techniques. The SF particles are found to be nearly 500 nm and decorated on RGO sheets as revealed by field emission scanning electron microscopy and transmission electron microscopy analysis. Fourier transform infrared and and Raman spectroscopy clearly show the presence of SF in the graphene sheet by the lower peak positions. Finally, ternary polymer composites of RGO/SF/PMMA are prepared by an in situ polymerization method. Magnetic and dielectric studies of the composite reveal that the presence of RGO/SF/PMMA lead to polarization effects contributing to dielectric loss. Also, RGO surrounding SF provides a conductive network in the polymer matrix which is in turn responsible for the magnetic loss in the composite. Thus, the permittivity as well as the permeability of the composite can be controlled by an appropriate combination of RGO and SF in PMMA. More than 99% absorption efficiency is achieved by a suitable combination of magneto-dielectric coupling in the X-band frequency range by incorporating 9 wt% of RGO and 1 wt% of SF in the polymer matrix.